ANALISIS YURIDIS TENTANG PEMBEBANAN PERTANGGUNG JAWABAN PIDANA YANG DILAKUKAN KORPORASI - Hidayahtullah, Yusuf; Jayakusuma, Zulfikar; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Forest and land fires that occur in the community or in other institutions such as Corvation often occur during the dry season, so that it is affected by individuals who improve land that is expected to save the lives of people who cause the disease. This type of research finds juridical research normative, because in this study the authors used literature studies. The data source that I use, primary data, secondary data, and tertiary, data merging techniques, in this study is to replace studio studies of the study of books, literature, notes and reports that relate to the problems that the authors examine. From the results of the study the problem of two main things that can be concluded. First, what is the determination of determining the payment of liability for the land and forest acquisition. Second, how is the liability of the sentence carried out by the company in the event of a vacancy? Authors' Suggestions, firstly Based on article 49 of Law Number 41 Year 1999 Concerning Licensing Related Rights or Permits responsible for forest fires in the area taken over, according to the case of PT Wahana Sumber Sawit Indah (WSSI) responsible for forest and land fires caused by negligence / neglect is not the business of H Thamrin Basri who is considered as the company's leader. PT Wahana is a source of beautiful palm oil Siak district responsible for the company is the company responsible for the company handling the vacancy of the company responsible for the assistance submitted by Mr. Thamrin Basri whose responsibility is not on target. Keywords: Criminal Liability Conducted by the Corporation